Ruthenium-cluster-loaded nitrogen-doped carbon-based composite catalytic material as well as preparation method and application thereof

By loading ruthenium clusters on the conductive carbon substrate and regulating its electronic configuration using nitrogen atoms, the proton exchange membrane electrolytic oxygen-analyzed catalyst is solved, and a proton exchange membrane electrolytic water anode material with high activity and simplified processes is achieved.

CN120158762APending Publication Date: 2025-06-17HANGZHOU NORMAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311721124.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-14
Publication Date
2025-06-17

AI Technical Summary

Technical Problem

The existing proton exchange membrane electrolytic oxygen-exciting catalysts have problems such as easy agglomeration, poor bonding with the matrix, and low catalytic activity, and the process flow of powder granule catalysts is complicated.

Method used

Through conductive polypyrrole as a bridge, the ruthenium cluster is tightly supported on the conductive carbon substrate, and the ruthenium cluster is anchored in situ to the surface of the carbon-based material through nitrogen atom regulation to form a nitrogen-doped carbon-based composite catalytic material supported by ruthenium clusters.

Benefits of technology

It solves the problem that ruthenium catalysts are prone to agglomeration and limited activity, simplifies the process flow, improves the conductivity and activity of catalytic materials, and has excellent electrochemical reaction catalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120158762A_ABST
    Figure CN120158762A_ABST
Patent Text Reader

Abstract

The invention relates to the field of electrochemical energy conversion, and discloses a ruthenium-cluster-loaded nitrogen-doped carbon-based composite catalytic material as well as a preparation method and application thereof. Comprising the following steps: step 1, taking a mixed aqueous solution of pyrrole and sodium p-toluenesulfonate as an electrolyte, taking a conductive carbon substrate material as a working electrode, and loading polypyrrole on the conductive carbon substrate material by adopting a constant potential deposition method to obtain a nitrogen-containing carbon material; and 2, dipping the nitrogen-containing carbon material in a ruthenium precursor solution, taking out, drying, calcining, pickling, and drying to obtain the ruthenium-cluster-loaded nitrogen-doped carbon-based composite catalytic material. The nitrogen-doped carbon-based composite catalytic material loaded with the ruthenium clusters has the advantages that the protruding wave morphology is achieved, the ruthenium clusters are anchored to the surface of the material, the excellent electro-catalysis oxygen evolution reaction performance is shown, and the nitrogen-doped carbon-based composite catalytic material loaded with the ruthenium clusters can be used as an oxygen evolution anode material for water electrolysis of a proton exchange membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical energy conversion, and particularly relates to a ruthenium cluster-loaded nitrogen-doped carbon-based composite catalytic material, a preparation method thereof, and an application thereof. Background Art

[0002] Proton exchange membrane water electrolysis has advantages such as high hydrogen production purity and high current density, and is an ideal water electrolysis hydrogen production technology. Its hydrogen production process includes anodic oxygen evolution reaction and cathodic hydrogen evolution reaction. Compared with the cathodic hydrogen evolution reaction, the anodic oxygen evolution reaction is a four-electron reaction process with a relatively high reaction energy barrier, which has become the main bottleneck for the development of this technology. Therefore, developing a highly active anodic oxygen evolution catalytic material to reduce the overpotential is a necessary condition for the industrial application of proton exchange membrane water electrolysis.

[0003] Due to the special strong acid environment of proton exchange membrane water electrolysis technology, the anodic oxygen evolution catalytic material is limited to iridium-based and ruthenium-based catalysts. For example, CN116926614A discloses a preparation method of an anodic oxygen evolution catalyst for proton exchange membrane water electrolysis, and the oxygen evolution catalyst is iridium oxide or ruthenium oxide or iridium oxide-ruthenium oxide, iridium oxide-transition metal oxide or ruthenium oxide-transition metal oxide. In the process of preparing the iridium oxide or ruthenium oxide oxygen evolution catalyst, carbonates or oxalates are used as co-precipitants to synthesize an oxygen evolution catalyst with a nanorod structure. For example, CN117004960A discloses an iridium-ruthenium catalyst, a preparation method thereof, an application thereof, and a proton exchange membrane water electrolysis cell. By mixing, separating, and calcining an iridium source and a ruthenium source, ruthenium oxide is doped into iridium oxide to synthesize an iridium-ruthenium catalyst with low iridium-ruthenium catalyst crystallinity and low iridium content.

[0004] Compared with iridium, ruthenium has a lower cost. Therefore, the development of ruthenium-based catalysts is more practically significant for the industrial application of anodic oxygen evolution catalytic materials for proton exchange membrane water electrolysis. However, at present, these mainstream anodic oxygen evolution catalysts for proton exchange membrane water electrolysis, ruthenium oxide and modified ruthenium oxide belong to powder particle catalysts, which require secondary drop coating, resulting in a cumbersome process; the use of adhesives also makes the conductivity of the catalyst poor and reduces the performance of the material; during long-term operation, there is also a problem of physical shedding of the catalyst. In addition, ruthenium oxide itself is prone to agglomeration, and its activity and stability have not yet met industrial requirements. Therefore, it is necessary to develop a new type of ruthenium-based catalytic material and preparation method to solve the above technical problems and promote its industrial production application. Summary of the Invention

[0005] In view of the problems of the ruthenium catalyst for oxygen evolution in proton exchange membrane electrolyzed water, such as easy agglomeration, weak binding to the substrate, low catalytic activity, and the cumbersome process of powder particle catalysts, the present invention provides a preparation method of a ruthenium cluster-loaded nitrogen-doped carbon-based composite catalytic material. By using nitrogen atoms as a bridge, ruthenium clusters are anchored on the carbon-based material, and the local electronic configuration of ruthenium clusters is adjusted through nitrogen atom regulation, solving the problems of easy agglomeration and limited activity of ruthenium catalysts. The highly active catalytic substance is in-situ grown on the surface of the self-supporting conductive carbon substrate, avoiding the process of secondary drop coating required for powder particle catalysts and solving the problem of cumbersome process flow.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A preparation method of a ruthenium cluster-loaded nitrogen-doped carbon-based composite catalytic material, characterized by comprising the steps:

[0008] Step 1, using a mixed aqueous solution of pyrrole and sodium p-toluenesulfonate as the electrolyte and a conductive carbon substrate material as the working electrode, and loading polypyrrole on the conductive substrate carbon material by a potentiostatic deposition method to obtain a nitrogen-containing carbon material;

[0009] Step 2, impregnating the nitrogen-containing carbon material in a ruthenium precursor solution, taking it out, drying, calcining, and then performing pickling and drying to obtain the ruthenium cluster-loaded nitrogen-doped carbon-based composite catalytic material.

[0010] The present invention uses conductive polypyrrole as a bridge and loads it tightly on the conductive carbon substrate by an electrodeposition method. Its constructed protruded wavy morphology improves the specific surface area of the material and increases the exposed active sites; using conductive polypyrrole as a bridge, ruthenium is adsorbed on the material surface by an impregnation method, and ruthenium is further bonded with nitrogen by calcination to in-situ anchor it on the surface of the carbon-based material; nitrogen doping adjusts the local electronic structure of ruthenium, accelerates its electron transfer speed, reduces its reaction energy barrier, and thus enhances its intrinsic activity; in addition, using the conductive carbon substrate as a self-supporting material, a nitrogen-doped carbon material loaded with ruthenium clusters as the active substance is grown on its surface, greatly solving the problems of poor contact between the catalytic material and the electrode surface, poor conductivity, and viscous interfacial gas products. Therefore, the material of the present invention has excellent electrochemistry reaction catalytic performance, is an ideal anode material for proton exchange membrane electrolyzed water, and helps to promote the industrial application of proton exchange membrane electrolyzed water.

[0011] Preferably, in Step 1, the deposition voltage of the potentiostatic deposition is 1-2V, and the electrodeposition time is 10-60min.

[0012] Preferably, the conductive carbon substrate material includes at least one of carbon paper, carbon cloth, graphite, or modified carbon paper, carbon cloth, and graphite materials.

[0013] Preferably, in step 1, the molar concentration of pyrrole in the mixed aqueous solution is 0.1-1M, and the molar concentration of sodium p-toluenesulfonate is 0.1-1M;

[0014] Preferably, the molar ratio of pyrrole to sodium toluenesulfonate is 1:0.8-1.2.

[0015] Preferably, the ruthenium precursor includes ruthenium acetate and / or ruthenium chloride; the ruthenium precursor solution is an aqueous solution of the ruthenium precursor, and the solute molar concentration is 0.03-0.1 mM.

[0016] In step 2, the impregnation time is 2-24 h.

[0017] Preferably, in step 2, the calcination is carried out at 700-1000 °C, the heating rate is 2-10 °C / min, and the calcination time is 1-5 h;

[0018] In step 2, the calcination environment is an inert gas, such as nitrogen, argon, etc.

[0019] In step 2, the pickling is carried out with at least one of sulfuric acid, nitric acid, hydrochloric acid, and hydrofluoric acid, the acid concentration is 0.1-1M; the pickling time is 2-24 h.

[0020] In step 1, the counter electrode is a graphite rod electrode, and the reference electrode is an Ag / AgCl electrode.

[0021] The present invention also provides a ruthenium cluster-loaded nitrogen-doped carbon-based composite catalytic material prepared according to the described preparation method.

[0022] The present invention also provides the application of the ruthenium cluster-loaded nitrogen-doped carbon-based composite catalytic material in proton exchange membrane electrolytic water oxygen evolution.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The present invention uses conductive polypyrrole as a bridge, and tightly loads it on the conductive carbon substrate by electrodeposition, and then in-situ anchors ruthenium on the surface of the carbon-based material through impregnation and calcination; under the combined action of nitrogen element, ruthenium anchoring and conductive carbon substrate, the problems of poor contact between the catalytic material and the electrode surface, poor conductivity, limited catalytic activity, and viscous interfacial gas products are greatly solved. Therefore, the material of the present invention has excellent electrochemistry reaction catalytic performance, is an ideal anode material for proton exchange membrane electrolytic water, and helps to promote the industrial application of proton exchange membrane electrolytic water.

[0025] (2) The present invention realizes the in-situ growth, morphology regulation and nitrogen doping regulation of ruthenium-based catalysts on conductive carbon substrates, enriches the synthesis and preparation technology of ruthenium-based catalysts, and at the same time simplifies the process flow, which greatly broadens its commercial application value. Brief Description of the Drawings

[0026] Figure 1 Scanning electron microscope image of the nitrogen-doped carbon material prepared in Comparative Example 1;

[0027] Figure 2 Scanning electron microscope image of the ruthenium cluster-loaded nitrogen-doped carbon-based composite catalytic material prepared in Example 2;

[0028] Figure 3 X-ray photoelectron spectroscopy image of the ruthenium cluster-loaded nitrogen-doped carbon-based composite catalytic material prepared in Example 2;

[0029] Figure 4 Linear sweep voltammogram of the catalytic performance of the ruthenium cluster-loaded nitrogen-doped carbon-based composite catalytic materials of Examples 1-4, Comparative Examples 1-2, and ruthenium oxide in Application Example 1. Detailed Description of the Invention

[0030] In order to make the objectives, technical solutions, and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. Those skilled in the art who make modifications or equivalent replacements based on the understanding of the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention shall be covered by the protection scope of the present invention.

[0031] The raw materials used in the following detailed description are all purchased from the market.

[0032] Example 1

[0033] After cleaning and drying a 1×3 cm graphite sheet, a two-electrode system was constructed. The graphite sheet (1×3 cm) and the platinum sheet (20×20 mm) were used as the working electrode and the counter electrode, respectively. The electrolytic solution was 0.1 M (NH4)2SO4 with a pH value of about 6.5 - 7.0. A DC voltage of +10 V was applied to the graphite electrode and maintained for 3 min. Subsequently, the graphite sheet was washed and dried in an oven at 60°C for 2 h to obtain a three-dimensional structured conductive graphite substrate material.

[0034] 0.1 M pyrrole, 0.1 M p-toluenesulfonic acid sodium salt, and 50 mL of ultrapure water were mixed and stirred thoroughly to form a 50 mL nitrogen-containing precursor solution. A three-electrode system was constructed. The working electrode was the three-dimensional structured conductive graphite substrate material, and the graphite rod and the Ag / AgCl electrode were used as the counter electrode and the reference electrode, respectively. The reaction was carried out at room temperature using the potentiostatic method (1.2 V) for 10 min. After washing and drying with ultrapure water, a nitrogen-containing carbon material was obtained.

[0035] Add 4 mL of 0.03 mM ruthenium acetate to a 10 mL sample bottle. Place the nitrogen-containing carbon material in the sample bottle and impregnate it at room temperature for 12 h. Then dry it in an oven at 55 °C. After drying, place it in a tube furnace. The gas atmosphere is nitrogen, and the heating rate is 5 °C / min. Calcinate it at 900 °C for 1 h. After calcination, immerse it in 1.0 M HCl aqueous solution for acid washing for 24 h, and then dry it in an oven to obtain the ruthenium cluster-loaded nitrogen-doped carbon-based composite catalytic material-1.

[0036] Example 2

[0037] After cleaning and drying a 1×3 cm graphite sheet, construct a two-electrode system. The graphite sheet (1×3 cm) and the platinum sheet (20×20 mm) serve as the working electrode and the counter electrode respectively. The electrolytic solution is 0.1 M (NH4)2SO4 with a pH value of about 6.5 - 7.0. Apply a DC voltage of +10 V to the graphite electrode and maintain it for 3 min. Subsequently, wash the graphite sheet and dry it in an oven at 60 °C for 2 h to obtain the three-dimensional structured conductive graphite substrate material.

[0038] Mix 0.1 M pyrrole, 0.1 M sodium p-toluenesulfonate with 50 mL of ultrapure water and stir well to form a 50 mL nitrogen-containing precursor solution. Construct a three-electrode system. The working electrode is the three-dimensional structured conductive graphite substrate material, and the graphite rod and the Ag / AgCl electrode serve as the counter electrode and the reference electrode respectively. The reaction is carried out at room temperature. Using the potentiostatic method (1.2 V) for 10 min, after washing and drying with ultrapure water, obtain the nitrogen-containing carbon material.

[0039] Add 4 mL of 0.08 mM ruthenium acetate to a 10 mL sample bottle. Place the nitrogen-containing carbon material in the sample bottle and impregnate it at room temperature for 12 h. Then dry it in an oven at 55 °C. After drying, place it in a tube furnace. The gas atmosphere is nitrogen, and the heating rate is 5 °C / min. Calcinate it at 900 °C for 1 h. After calcination, immerse it in 1.0 M HCl aqueous solution for acid washing for 24 h, and then dry it in an oven to obtain the ruthenium cluster-loaded nitrogen-doped carbon-based composite catalytic material-2.

[0040] Example 3

[0041] Referring to Example 2, change the calcination temperature from 900 °C to 700 °C to obtain the ruthenium cluster-loaded nitrogen-doped carbon-based composite catalytic material-3.

[0042] Example 4

[0043] Referring to Example 2, change the calcination temperature from 900 °C to 1000 °C to obtain the ruthenium cluster-loaded nitrogen-doped carbon-based composite catalytic material-4.

[0044] Comparative Example 1

[0045] After cleaning and drying the 1×3cm graphite sheet, a two-electrode system was constructed, with the graphite sheet (1×3cm) and platinum sheet (20×20mm) as the working electrode and counter electrode, respectively. The electrolytic solution was 0.1M (NH4)2SO4, with a pH value of about 6.5-7.0. A +10V DC voltage was applied to the graphite electrode and maintained for 3 minutes. The graphite sheet was then washed and dried in an oven at 60°C for 2 hours. The resulting graphite sheet was a three-dimensional conductive graphite substrate material.

[0046] 4 mL of 0.08 mM ruthenium acetate was added to a 10 mL sample bottle, and the three-dimensional structured conductive graphite substrate material was placed in the sample bottle and immersed at room temperature for 12 hours, and then placed in a 55°C oven to dry; after drying, it was placed in a tubular furnace with a nitrogen atmosphere, a heating rate of 5°C / min, and calcined at 900°C for 1 hour; after calcination, it was immersed in a 1.0 M HCl aqueous solution for acid washing for 24 hours, and then dried in an oven to obtain a carbon material loaded with ruthenium clusters.

[0047] Comparative Example 2

[0048] After cleaning and drying the 1×3cm graphite sheet, a two-electrode system was constructed, with the graphite sheet (1×3cm) and platinum sheet (20×20mm) as the working electrode and counter electrode, respectively. The electrolytic solution was 0.1M (NH4)2SO4, with a pH value of about 6.5-7.0. A +10V DC voltage was applied to the graphite electrode and maintained for 3 minutes. The graphite sheet was then washed and dried in an oven at 60°C for 2 hours. The resulting graphite sheet was a three-dimensional conductive graphite substrate material.

[0049] 0.1M pyrrole, 0.1M sodium p-toluenesulfonate and 50mL ultrapure water were mixed and stirred thoroughly to form 50mL nitrogen-containing precursor solution. A three-electrode system was constructed, with the working electrode being a three-dimensional conductive graphite substrate material, the graphite rod and the Ag / AgCl electrode being the counter electrode and the reference electrode, respectively. The reaction was carried out at room temperature using a constant potential method (1.2V) for 10min, and the nitrogen-containing carbon material was obtained after washing with ultrapure water and drying.

[0050] The nitrogen-containing carbon material was placed in a tubular furnace with a nitrogen atmosphere and a heating rate of 5°C / min. It was calcined at 900°C for 1h, and then washed with ultrapure water and dried to obtain a nitrogen-doped carbon material.

[0051] The nitrogen-doped carbon material of Comparative Example 2 was characterized by scanning electron microscopy. The results are as follows: Figure 1 As shown in FIG. 1 , the polypyrrole in the obtained nitrogen-doped carbon material is stacked by numerous spherical particles to form a protruding wave morphology. The nitrogen-doped carbon-based composite catalytic material loaded with ruthenium clusters in Example 2 was characterized by scanning electron microscopy. The results are shown in FIG. Figure 2As shown, the obtained material maintains a protruding wavy morphology, and ruthenium clusters are uniformly loaded on the surface of nitrogen-doped carbon. X-ray photoelectron spectroscopy image analysis was performed on the nitrogen-doped carbon-based composite catalytic material loaded with ruthenium clusters in Example 2. As Figure 3 shown, ruthenium is bonded to nitrogen, and strong bonding occurs between ruthenium clusters and nitrogen-doped carbon. The ruthenium clusters are tightly anchored on the surface of nitrogen-doped carbon.

[0052] Application Example 1

[0053] Linear sweep voltammetry tests were carried out on the nitrogen-doped carbon-based composite catalytic materials loaded with ruthenium clusters prepared in Examples 1-4, the ruthenium cluster-doped carbon material in Comparative Example 1, the nitrogen-containing carbon material in Comparative Example 2, and the commercial catalyst ruthenium oxide in a 0.5 M H2SO4 electrolyte solution. The specific test process was to construct a three-electrode system, using a graphite rod and an Ag / AgCl electrode as the counter electrode and reference electrode respectively, and the prepared catalytic electrode material as the working electrode, with the electrolyte being 0.5 M H2SO4.

[0054] The results are as Figure 4 shown. It can be seen that the nitrogen-doped carbon-based composite catalytic materials loaded with ruthenium clusters obtained in Examples 1-4 have excellent electrocatalytic oxygen evolution performance, far higher than those in Comparative Examples 1-2 and the commercial catalyst ruthenium oxide.

[0055] Specifically, compared with the nitrogen-doped carbon-based composite catalytic materials loaded with ruthenium clusters in Examples 1-4, different ruthenium impregnation concentrations and calcination temperatures have a slight impact on their catalytic performance. Among them, the performance of the nitrogen-doped carbon-based composite catalytic material -2 loaded with ruthenium clusters in Example 2 is the best, with a ruthenium impregnation concentration of 0.08 mM and a calcination temperature of 900 °C. Considering the cost factor, the material already has excellent electrocatalytic oxygen evolution performance under this low-concentration ruthenium impregnation solution, and increasing the ruthenium impregnation concentration does not significantly improve the performance. Therefore, it is not meaningful to continue increasing the ruthenium impregnation concentration. Among the calcination temperatures of 700-1000 °C, the material calcined at 900 °C has shown the best performance.

[0056] When comparing the nitrogen-doped carbon-based composite catalytic material -2 loaded with ruthenium clusters in Example 2 with the carbon material loaded with ruthenium clusters in Comparative Example 1, when there is no nitrogen as a bridge, even if the same amount of ruthenium is loaded, the catalytic effect of the product is not very ideal.

[0057] When comparing the nitrogen-doped carbon-based composite catalytic material -2 loaded with ruthenium clusters in Example 2 with the nitrogen-doped carbon material in Comparative Example 2, compared with the single nitrogen doping, the anchoring of ruthenium clusters can greatly improve the material performance.

[0058] As described above, it is only the preferred specific embodiment of the present invention, and the protection scope of the present invention is not limited thereto. Any simple variation or equivalent replacement of the technical solution that can be obviously obtained by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope of the present invention.

Claims

1. A preparation method of a ruthenium cluster-loaded nitrogen-doped carbon-based composite catalytic material, characterized in that, Including the steps: Step 1: Using a mixed aqueous solution of pyrrole and sodium p-toluenesulfonate as the electrolyte and a conductive carbon substrate material as the working electrode, polypyrrole is loaded onto the conductive carbon substrate material by a potentiostatic deposition method to obtain a nitrogen-containing carbon material; Step 2: Immerse the nitrogen-containing carbon material in a ruthenium precursor solution, take it out, dry it, calcine it, and then perform pickling and drying to obtain the ruthenium cluster-loaded nitrogen-doped carbon-based composite catalytic material.

2. The preparation method of the ruthenium cluster-loaded nitrogen-doped carbon-based composite catalytic material according to claim 1, characterized in that, In Step 1, the deposition voltage of the potentiostatic deposition is 1 - 2V, and the electrodeposition time is 10 - 60min.

3. The preparation method of the ruthenium cluster-loaded nitrogen-doped carbon-based composite catalytic material according to claim 1, characterized in that, The conductive carbon substrate material includes at least one of carbon paper, carbon cloth, graphite, or modified carbon paper, carbon cloth, and graphite materials.

4. The preparation method of the ruthenium cluster-loaded nitrogen-doped carbon-based composite catalytic material according to claim 1, characterized in that, In Step 1, the molar concentration of pyrrole in the mixed aqueous solution is 0.1 - 1M, the molar concentration of sodium p-toluenesulfonate is 0.1 - 1M, and the molar ratio of pyrrole to sodium toluenesulfonate is 1:0.8 - 1.

2.

5. The preparation method of the ruthenium cluster-loaded nitrogen-doped carbon-based composite catalytic material according to claim 1, characterized in that, The ruthenium precursor includes ruthenium acetate and / or ruthenium chloride; the ruthenium precursor solution is an aqueous solution of the ruthenium precursor, and the solute molar concentration is 0.03 - 0.1mM; the impregnation time in Step 2 is 2 - 24h.

6. The preparation method of the ruthenium cluster-loaded nitrogen-doped carbon-based composite catalytic material according to claim 1, characterized in that, In Step 2, the calcination temperature is 700 - 1000°C, the heating rate is 2 - 10°C / min, and the calcination time is 1 - 5h; The calcination environment in Step 2 is an inert gas.

7. The preparation method of the ruthenium cluster-loaded nitrogen-doped carbon-based composite catalytic material according to claim 1, characterized in that, In Step 2, pickling is performed using at least one of sulfuric acid, nitric acid, hydrochloric acid, and hydrofluoric acid, the acid concentration is 0.1 - 1M; the pickling time is 2 - 24h.

8. The preparation method of the ruthenium cluster-loaded nitrogen-doped carbon-based composite catalytic material according to claim 1, characterized in that, In Step 1, the counter electrode is a graphite rod electrode, and the reference electrode is an Ag / AgCl electrode.

9. A ruthenium cluster-loaded nitrogen-doped carbon-based composite catalytic material prepared by the preparation method according to any one of claims 1-8.

10. Application of the ruthenium cluster-loaded nitrogen-doped carbon-based composite catalytic material according to claim 9 in oxygen evolution of proton exchange membrane electrolytic water.

Citation Information

Patent Citations

  • Preparation method of proton exchange membrane water electrolysis oxygen evolution catalyst

    CN116926614A

  • Iridium ruthenium catalyst, preparation method and application thereof, and proton exchange membrane water electrolyser

    CN117004960A